1985
DOI: 10.1016/0005-2760(85)90052-9
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of rat platelet and serum phospholipase A2 activities

Abstract: Rat platelet lysate contained appreciable phospholipase A, activity. In agreement with literature data this enzymatic activity eluted in the void volume of a Sephadex G-100 column. When the void volume peak was chromatographed over a Matrex gel blue A column, part of the phospholipase A, activity ran through, whereas the remainder was bound to the gel. The latter activity could be eluted with buffers containing a high salt concentration. In contrast, phospholipase A, activity solubilized from rat platelet lysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Although our culture medium contains 5% calf bovine serum (v/v), which is known to contain PLA2 activity (Aarsman et al 1985;Nishijima et al 1983), our results from PLA2 assay revealed that its contribution did not exceed 4% of total PLA2 activity measured in hRPE growth medium (data not shown). We can therefore conclude that the PLA2 activity detected in hRPE growth medium was attributable to active enzyme secretion by hRPE cells.…”
Section: Cultured Hrpe Cells Contain Different Pla2-active Fractionsmentioning
confidence: 85%
“…Although our culture medium contains 5% calf bovine serum (v/v), which is known to contain PLA2 activity (Aarsman et al 1985;Nishijima et al 1983), our results from PLA2 assay revealed that its contribution did not exceed 4% of total PLA2 activity measured in hRPE growth medium (data not shown). We can therefore conclude that the PLA2 activity detected in hRPE growth medium was attributable to active enzyme secretion by hRPE cells.…”
Section: Cultured Hrpe Cells Contain Different Pla2-active Fractionsmentioning
confidence: 85%
“…Preparation of a platelet suspension from I0 ml rat blood and extraction of phospholipase A2 from the platelets was performed as described earlier [17].…”
Section: Isolation Of Rat Platelet Phospholipase Amentioning
confidence: 99%
“…These analyses raise the question, what is the in vivo target substrate of platelet phospholipase A2? Aarsman et al [44] showed that the phospholipase A, from platelet Table 1. Effect of inhibitors on phospholipase A2.…”
Section: Resultsmentioning
confidence: 99%